2022
DOI: 10.18231/j.ijce.2022.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation using finite element analysis of three root canal preparation tapers on stresses within the roots

Abstract: The stress distribution on endodontically treated teeth varies with different tapers of root canal preparation and thus the fracture resistance. The objective of this study was to evaluate the stress distribution on endodontically treated teeth between three different tapers of root canal preparation during simulated application of loads on the teeth. In this study, mandibular incisors with straight and mature canals were chosen, cleaning and shaping was done using Hyflex Nickel Titanium (NiTi) rotary instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…concluded that the peri-cervical dentin region had maximum VM stresses in all the three designs. [ 3 ] The findings are similar to our results. Smoljan et al .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…concluded that the peri-cervical dentin region had maximum VM stresses in all the three designs. [ 3 ] The findings are similar to our results. Smoljan et al .…”
Section: Discussionsupporting
confidence: 92%
“…To imitate clinical condition, the FEA models were deliberated with the addition of PDL and alveolar bone. [ 3 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation